Atuação fisioterapêutica no fogo selvagem (Pênfigo) - de Oliveira Ribeiro, Fernando Augusto; Cardoso, Denise da Silva; Benito, Caroline Ruiz; Dias, Mirela Barros; Tebet, Karina Alonso; Rodrigues, Diana Pache; Lima, Patrícia da Silva (Multitemas, 2016)
__